A Study of the Reactivity of (Aza‐)Quinone Methides in Selective C6‐Alkylations of Indoles. Issue 20 (2nd September 2020) - Yan, Jiyao; Zhang, Zhihan; Chen, Min; Lin, Zhenyang; Sun, Jianwei
Abstract: The kinetic and thermodynamic features of indole N1‐ and C6‐alkylation reactions with (aza‐)quinone methides have been studied. The electrophilic reactivity of these quinone methides have also been compared for the first time by both experiments and DFT calculations. The indole N1‐alkylation is typically kinetically favorable, but the C6‐alkylation is more thermodynamically favorable. With suitable conditions, the C6‐alkylation could be achieved with high efficiency and selectivity. Among these quinone methides, the reactivity increases from aza‐p‐QMs to o‐QMs. The results not only provide access to a range of valuable triarylmethanes, but also guide future development of new reactions with these versatile electrophiles. Abstract : Phosphoric Acid Organocatalysis : Brønsted acid catalyzed selective C6‐alkylations with (aza‐)quinone methides provides important access to valuable triarylmethanes. The reactivities of aza‐p ‐QMs, p ‐QMs and o ‐QMs have also been compared for the first time enabled by both experiments and DFT studies.